The Experience of Essential Tremor Caregivers: Burden and Its Correlates - Morgan, Sarah; Kellner, Sarah; Gutierrez, Jesus; Collins, Kathleen; Rohl, Brittany; Migliore, Fanny; Cosentino, Stephanie; Huey, Edward D.; Louis, Elan D.; Monin, Joan K. (Frontiers in Neurology, 2017)
Background Essential tremor (ET) is associated with physical and cognitive impairments, as well as embarrassment, avoidance of social settings, and related difficulties that negatively impact the lives of patients. In similar disease contexts, burden on friends and relatives acting as caregivers has been noted and has well-documented implications. There has been no study examining caregiver burden related to ET. Methods Data were gathered from 55 ET participants enrolled in a clinical study and their caregivers. The Zarit Burden Interview (ZBI-12) was used to assess caregiver burden. To assess clinical features that may be associated with burden, we collected several variables including the Montreal Cognitive Assessment (MoCA), self-reported tremor disability, a videotaped neurological examination, questionnaires assessing ET participants’ suffering, caregivers’ perceptions of that suffering, and both caregiver and ET participant depressive symptoms. Spearman’s correlations were performed between caregiver burden and clinical features, and we created a multivariate linear regression model predicting caregiver burden. Results Many ET caregivers provide little to no care and experience little to no burden. However, some caregivers (11%) provide over 25 hours of care/week, and 13% experience high levels of burden. Caregivers most commonly provided assistance with writing and cooking. Increased burden was associated with the ET participants’ decreased cognition, more caregiving tasks, more hours/week of caregiving activities, a longer duration of care, more ET participant falls/year, more medications taken by the ET participant, and more depressive symptoms in both the ET participant and the caregiver (all p <0.05). ET participants’ suffering and their caregivers’ perceptions of suffering were both associated with increased burden. Neither tremor severity score nor self-reported tremor disability score was associated with increased caregiver burden. Using a multivariate linear regression model, we found that caregivers’ increased perception of their partners’ suffering was the best predictor of caregiver burden. Conclusions While not all relatives and friends of ET patients provide extensive care or experience high burden, there is a group reporting high levels of caregiver burden that requires the attention and counseling of clinicians. This burden is associated with primarily non-tremor symptoms of ET and with caregivers’ perception that their partners are suffering.